Child poverty on the island of Ireland - Helen Russell; Bertrand Maître; Anousheh Alamir; Eva Slevin (The Economic and Social Research Institute (ESRI), 2025)
The effects of poverty in childhood can last a lifetime. Research shows that children living in poverty have lower levels of health and wellbeing, attain lower levels of education, have lower levels of occupational attainment and are more likely to be poor in adulthood. In this report, we focus on child poverty on the island of Ireland. While child poverty in each jurisdiction has been studied separately, there is an absence of comparative research. A comparative analysis of this sort can help to identify the features of the two systems that are influential in preventing or exacerbating child poverty. In both Ireland and the UK, children have had the highest income poverty rates of all age groups over the past ten years. While child poverty rates worsened over the past decade in the UK (Joseph Rowntree Foundation, 2024), they remained relatively stable in Ireland over the 2000s when measured by household income. However, rates of child material deprivation rose and fell following the pattern of economic boom, bust and recovery (Roantree et al., 2024). This report sets out to compare child poverty across the two jurisdictions, using a mixed-methods approach with harmonised national survey data on incomes and living standards (SILC and FRS), as well as consultations with stakeholders from both jurisdictions to help identify policy issues most relevant for child poverty in each jurisdiction. The study addresses three research questions: 1. Which groups of children are most vulnerable to poverty in the two jurisdictions? 2. What is the role of household labour market situation and social background in shaping the risk of child poverty in Ireland and Northern Ireland? 3. How do policy approaches to addressing child poverty differ in Ireland and Northern Ireland and how do these policies influence the patterns of child poverty observed? The report uses two measures of poverty: Income poverty, which is having a disposable income that is less than 60 per cent of median income for Ireland or the UK; Material deprivation is measured by the lack of access to five items that are considered as standard within societies and are common to the two data sources, such as arrears on bills or inability to keep the home adequately warm. The consideration of deprivation is important because income alone does not capture the variation in needs and long-term resources of households.
Keywords: 330; Child poverty; Household income; Social situation; Poverty reduction; Comparison; Ireland; Northern Ireland; Kinderarmut; Haushaltseinkommen; Soziale Lage; Armutsbekämpfung; Vergleich; Irland; Nordirland